Motor neurons control blood vessel patterning in the developing spinal cord - Himmels, Patricia; Paredes Ugarte, Isidora B.; Adler, Heike; Karakatsani, Andromachi; Luck, Robert; Marti, Hugo; Ermakova, Olga; Rempel, Eugen; Ruiz de Almodóvar, Carmen (Nature Communications, 2017)
Formation of a precise vascular network within the central nervous system is of critical importance to assure delivery of oxygen and nutrients and for accurate functionality of neuronal networks. Vascularization of the spinal cord is a highly stereotypical process. However, the guidance cues controlling blood vessel patterning in this organ remain largely unknown. Here we describe a new neuro-vascular communication mechanism that controls vessel guidance in the developing spinal cord. We show that motor neuron columns remain avascular during a developmental time window, despite expressing high levels of the pro-angiogenic vascular endothelial growth factor (VEGF). We describe that motor neurons express the VEGF trapping receptor sFlt1 via a Neuropilin-1-dependent mechanism. Using a VEGF gain-of-function approach in mice and a motor neuron-specific sFlt1 loss-of-function approach in chicken, we show that motor neurons control blood vessel patterning by an autocrine mechanism that titrates motor neuron-derived VEGF via their own expression of sFlt1.
Published 6 Mar 2017
Gesehen am 22.06.2018